2019
DOI: 10.1016/j.apenergy.2019.113463
|View full text |Cite
|
Sign up to set email alerts
|

Alternative and sustainable heat production for drinking water needs in a subarctic climate (Nunavik, Canada): Borehole thermal energy storage to reduce fossil fuel dependency in off-grid communities

Abstract: Highlights-First-time design of borehole thermal energy storage in a subarctic climate -Best scenarios provide 50 % solar fraction and 60 % heat recovery at the 3 rd year -Annual savings of 7 000 l of diesel and 19 tonnes of equivalent CO2 are achieved -A novel type of borehole connection reduces advection heat loss by 60 % -Underground storage is a key technology towards energy and food security in the Arctic ABSTRACTThe development of renewable energy technologies in the Arctic faces technical barriers mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Thermal conductivity of gabbro was measured in another case study and ranged between 1.65 and 2.29 W m −1 K −1 [45], which is consistent with our results. Shale samples have an average thermal conductivity ranging between 2.4 and 2.9 W m −1 K −1 (Table 2), which is in agreement with a value of 2.8 W m −1 K −1 measured for other samples of similar lithology in the St. Lawrence lowlands [10,12,44,46]. The calcarenite sample has the highest thermal conductivity among all the samples collected in the quarry, with a value of 3.5 W m −1 K −1 .…”
Section: Subsurface Thermal Conductivitysupporting
confidence: 87%
See 2 more Smart Citations
“…Thermal conductivity of gabbro was measured in another case study and ranged between 1.65 and 2.29 W m −1 K −1 [45], which is consistent with our results. Shale samples have an average thermal conductivity ranging between 2.4 and 2.9 W m −1 K −1 (Table 2), which is in agreement with a value of 2.8 W m −1 K −1 measured for other samples of similar lithology in the St. Lawrence lowlands [10,12,44,46]. The calcarenite sample has the highest thermal conductivity among all the samples collected in the quarry, with a value of 3.5 W m −1 K −1 .…”
Section: Subsurface Thermal Conductivitysupporting
confidence: 87%
“…However, the impact of groundwater flow on underground thermal energy storage systems is negative because it increases heat loss around GHEs used as a heat storage medium. Giordano and Raymond [10] demonstrated that~10% of the energy lost by the bore field of an underground energy storage system can be due to advection when the Darcy flux is 8 × 10 −7 m s −1 , while this heat loss can be reduced bỹ 60 % if the connection and layout of the GHEs is designed considering the magnitude and direction of groundwater flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess electrical energy can heat a thermal reservoir, which can then release heat when required after an extended period. Thermal underground storage has been tested under sub-Arctic conditions but not in Arctic areas with permafrost [29]. For short-term or immediate solutions, water can be electrically heated and fed into the district heating system [26].…”
Section: Energy Storagementioning
confidence: 99%
“…Geothermal investigations with a focus on the Canadian northern communities facing critical energy challenges have additionally been carried out (e.g., Comeau et al 2017;Giordano and Raymond 2019;Grasby et al 2013;Gunawan et al 2020;Majorowicz and Grasby 2014;Majorowicz and Minea 2015b;Minnick et al 2018). These studies indicate promising geothermal energy development for the off-grid communities due to the cold climate and the high energy cost.…”
mentioning
confidence: 99%